Protocol for 3D bioprinting of a 3D in vitro model of neuroblastoma - Mehdi Salar Amoli; Sarah Rezapourdamanab; Linqi Jin; Melissa A. Cadena; Kaveeta Kaw; Vani Sridhar; Mostafa Meselhe; Sarah Krikor; Morteza Mahmoudi; Liqun Ning; Jenny Shim; Martin L. Tomov; et al. (STAR Protocols)
Summary: Here, we present a protocol for developing an in vitro 3D model of neuroblastoma through bioprinting, incorporating key components of the tumor microenvironment (TME), including vasculature and cancer cell line spheroids. We describe steps for the preparation, bioprinting, and evaluation of tumor models and their use to assess the impact of TME on solid tumor behavior. We report procedures for bioink preparation, bioprinting, the measurement of mechanical properties and fidelity, as well as the viability of different cell types and their interactions.For complete details on the use and execution of this protocol, please refer to Ning et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.